2018
DOI: 10.1371/journal.pone.0208942
|View full text |Cite
|
Sign up to set email alerts
|

Users’ preferences and design recommendations to promote engagements with mobile apps for diabetes self-management: Multi-national perspectives

Abstract: Background Mobile phone applications (apps) offer motivation and support for self-management of diabetes mellitus (DM), but their use is limited by high attrition due to insufficient consideration of end-users perspectives and usability requirements. This study aimed to examine app usage and feature preferences among people with DM, and explore their recommendations for future inclusions to foster engagement with diabetes apps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 63 publications
2
51
0
3
Order By: Relevance
“…Specific features and educational content in My Care Hub were chosen based on users' needs and preferences 27 . This is an added strength of the app which is often lacking in many health apps that are developed without considering the needs of the end users or guidelines for the management of such diseases 59,60 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specific features and educational content in My Care Hub were chosen based on users' needs and preferences 27 . This is an added strength of the app which is often lacking in many health apps that are developed without considering the needs of the end users or guidelines for the management of such diseases 59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…An expert advisory group comprising diabetes educators, endocrinologists, health researchers and app developers worked as a team to make decisions regarding My Care Hub. Implications of the users' needs analysis study findings and effectiveness of identified health behavioural change interventions were discussed by the team 27 . Results were prioritized, adjusted and refined before a final agreement on the selection of My Care Hub features, design and content in order to meet the requested needs of users as much as possible.…”
Section: Health Behavioural Change Theory Maximizing the Potential Ementioning
confidence: 99%
See 2 more Smart Citations
“…Digital and social technologies (eg, social media, smartphone apps, and wearable devices) have promising potential for achieving rapid and widespread health behavior change. Social media has been used to change and predict a number of health-related behaviors, including HIV testing and sexually transmitted diseases, suicide prevention, car crashes, and opioid-related emergency department visits [ 1 - 7 ]; Fitbits and self-tracking devices have been proposed as intervention tools to increase exercise [ 8 , 9 ] and reduce stress; health systems and insurers have integrated wearable device, social media and patient health/medical data to try to improve clinical outcomes [ 10 , 11 ]; and smartphone apps have be studied for their potential to improve a variety of health behaviors and outcomes, such as weight loss and diabetes self-management [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%